The effect of particle size on the genotoxicity of gold nanoparticles. Issue 3 (7th November 2016) - Xia, Qiyue; Li, Hongxia; Liu, Ying; Zhang, Shuyang; Feng, Qiyi; Xiao, Kai
Abstract: Despite the increasing biomedical applications of gold nanoparticles (AuNPs), their toxicological effects need to be thoroughly understood. In the present study, the genotoxic potential of commercially available AuNPs with varying size (5, 20, and 50 nm) were assessed using a battery of in vitro and in vivo genotoxicity assays. In the comet assay, 20 and 50 nm AuNPs did not induce obvious DNA damage in HepG2 cells at the tested concentrations, whereas 5 nm NPs induced a dose‐dependent increment in DNA damage after 24‐h exposure. Furthermore, 5 nm AuNPs induced cell cycle arrest in G1 phase in response to DNA damage, and promoted the production of reactive oxygen species (ROS). In the chromosomal aberration test, AuNPs exposure did not increase in the frequency of chromosomal aberrations in Chinese hamster lung (CHL) cells. In the standard in vivo micronucleus test, no obvious increase in the frequency of micronucleus formation was found in mice after 4 day exposure of AuNPs. However, when the exposure period was extended to 14 days, 5 nm AuNPs presented significant clastogenic damage, with a dose‐dependent increase of micronuclei frequencies. This finding suggests that particle size plays an important role in determining the genotoxicity of AuNPs. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 710–719, 2017.